2000
DOI: 10.1021/ja9920967
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale ab Initio Quantum Chemical Calculation of the Intermediates in the Soluble Methane Monooxygenase Catalytic Cycle

Abstract: Ab initio DFT quantum chemical methods are applied to study intermediates in the catalytic cycle of soluble methane monooxygenase hydroxylase (MMOH), a dinuclear iron-containing enzyme that converts methane and dioxygen selectively to methanol and water. The quantum chemical models reproduce reliably the X-ray crystallographic coordinates of the active site for the oxidized diiron(III) and reduced diiron(II) states to a high degree of structural precision. The results inspired a reexamination of the X-ray stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
210
1
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(227 citation statements)
references
References 60 publications
12
210
1
4
Order By: Relevance
“…Recent kinetic studies and theoretical calculations have suggested the presence of additional intermediates (6,9,10). For example, proton transfer steps have been observed in the formation and decay of H peroxo , a result consistent with a protonated peroxo intermediate in the mechanism (9).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Recent kinetic studies and theoretical calculations have suggested the presence of additional intermediates (6,9,10). For example, proton transfer steps have been observed in the formation and decay of H peroxo , a result consistent with a protonated peroxo intermediate in the mechanism (9).…”
mentioning
confidence: 72%
“…Formation of a superoxide species has also been proposed to be the first irreversible step in the reductive activation in a number of other oxygenactivating enzymes (12,15,16). Recent density functional theory (DFT) calculations have identified a possible superoxo intermediate species with an energy comparable with that of H peroxo (10). Further work is required to characterize the early dioxygen activation intermediates, clarify the relationship between kinetic and equilibrium isotope effects, and gain additional insights into the nature of the first irreversible step in the reaction.…”
Section: Analysis Of the Oxygen-18 Kinetic Isotope Effects: Constrainmentioning
confidence: 99%
“…Ab initio calculations provide a wealth of detail that is not available from experiment and a degree of confidence in the results that is not available from more empirical approaches. In systems such as methane monooxygenase, in which a substantial number of careful calculations have been performed by several groups (81,(91)(92)(93)(94)(95)(96) and close contact with experiment has been achieved for many aspects of the catalytic process, a comprehensive picture of the functioning of the enzyme is beginning to be assembled by means of the interaction of theory and experiment. Last, the coupling of ab initio quantum QM͞MM methods with simulation and protein structure prediction techniques permits investigation of events in which reactive chemistry is coupled to substantial conformational changes, such as the catalytic loop motion in triose phosphate isomerase (82).…”
Section: Applicationsmentioning
confidence: 99%
“…Extended x-ray absorption fine structure (EXAFS) analysis of Q has found a short FeOFe distance of 2.5 Å, which has led us to propose an [Fe IV 2 ( -O) 2 ] diamond core structure (6). Density functional theory (DFT) calculations from a number of groups also support the viability of such an intermediate (7)(8)(9)(10)(11). Although several mononuclear oxoiron(IV) complexes have been structurally characterized (12), thus providing valuable information regarding the catalytic mechanism of mononuclear nonheme iron enzymes (13) 3 [L c , tris(5-ethyl-2-pyridylmethyl)amine] (1c, Scheme 1) (14).…”
mentioning
confidence: 97%